A promising alternative: examining TVS tellurite glass for gamma radiation shielding applications - Uosif, M. A. M.; Issa, Shams A. M.; Ene, Antoaneta; Mostafa, A. M. A.; Atta, Ali; Badawi, Ali; El Agammy, E. F.; Zakaly, Hesham M. H. (Frontiers in Materials, 2023)
Radiation shielding is crucial in many types of medical, industrial, and nuclear facilities due to the widespread usage of radioactive isotopes. In this research, we examine the impact of tellurite 65TeO2–(35-x)V2O5-xSm2O3 glasses, where x ranges from 0.1 to 5 mol%, for its nuclear security and radiation shielding versus gamma attenuation capabilities. For gamma, the effect that the systematic replacement of Sm2O3 with V2O5 has on the shielding qualities was dissected in great depth. In addition, comparative research was carried out using the most recent borate glasses and the typical shielding materials considered the industry standard. In this study, we utilized the FLUKA algorithm and the FLAIR graphical interface to calculate the attenuation coefficients of glass compositions in the 65TeO2–(35-x)V2O5-xSm2O3system. The gamma energies of 0.356, 0.662, 1.332, and 2.614 MeV, commonly used in gamma shielding investigations, were selected as the radiation source. A comparison between the simulation results by FLUKA and theoretical calculations for mass attenuation coefficients demonstrated excellent agreement, confirming the reliability and accuracy of the FLUKA simulation method. The findings of the current research point to the fact that the TVS5 sample has the highest GMAC and lowest GHVL and GMFP, among other glasses. This points to the possibility that the TVS5 sample might be used in radiation shielding activities, which would result in increased nuclear safety.